The Influence of Stim-HOTs Learning Model Toward Student’s Critical Thinking Ability Reviewed from Academic Ability - Fida Alya Noor Rahmah; Slamet Santosa; Dwi Oetomo (Universitas Sebelas Maret, 2020)
Critical thinking abilities are one of the needed thinking skills to face the challenges of the 21st century. This research aims to determine the influence of the Stim-HOTs learning model toward student's critical thinking ability reviewed from the academic ability. Stim-HOTs is a learning model that can stimulate student's higher-order thinking skills, one of which is critical thinking. This research was a quasi-experimental research with posttest only nonequivalent control group design. The population of this research was all of the 11th-grade students of MIPA in SMA Negeri 5 Surakarta academic year 2019/2020. This research, using 2 classes for the sample, one class using Stim-HOTs learning model as experiment class, and the other class using discovery learning model as control class. The data were collected through a critical thinking essay instrument developed by Prihatiningsih that has been through expert validation. The data that has been tested for normality and homogeneity were analyzed by two-way ANOVA to test the hypothesis. The result using ANOVA two ways test shows 1) critical thinking ability based on learning model has a significant value higher than 0,050, 2) critical thinking based on academic ability has a significant value higher than 0,050, and 3) critical thinking based on learning model and academic ability has a significant value lower than 0,050. The research concluded that 1) Stim-HOTs learning model had a significant effect on critical thinking ability, 2) student's academic ability had a significant effect on critical thinking ability, and 3) there is no interaction between Stim-HOTs model and student's academic ability toward critical thinking ability.